The Effectiveness of Solution-Focused Brief Therapy Group Counseling to Improve Students’ Self-Concepts (Jurnal Bimbingan Konseling, 2019)
This study aimed to examine the effectiveness of SFBT group counseling on students’ self-concepts. To purse this objective, this study applied One Group pre-test – post-test design to 8 students of Public Senior High School 1 Lemahabang who had low self-concepts. The data of these subjects were collected using Tennese Self Concept Scale (TSCS) instrument and were analyzed using wilcoxon test. The results showed that SFBT group counseling was effective to fully improve the students’ self-concepts, and partially in each aspect of self-concepts, namely individual’s physical, ethical moral, personal, family, social, and self-criticism. At last, the discussion of this article is directed to the review of SFBT effectiveness to improve SMA students’ self-concepts.